Islamic Monetary System: Foundations Normative Pillars and Implementation Prospects in the Modern Era - Fattah, Abdul; Janwari, Yadi; Al-Hakim, Sofian (Yayasan Mentari Madani, 2025)
Recurrent global financial crises, such as the 1997 Asian crisis, the 2008 subprime mortgage crisis, and the economic uncertainty of the post-COVID-19 pandemic, highlight the structural weaknesses of the conventional debt- and interest-based monetary system that often fuels imbalances between the monetary and real sectors and encourages speculative behavior. In response, the Islamic monetary system exists as a normative and practical alternative that emphasizes justice, stability, and social welfare through the prohibition of usury, gharar, and maysir, as well as the linking of money to real economic activities. This article examines the philosophical foundations, normative pillars, and operational principles of the Islamic monetary system, highlighting the role of classical scholars such as al-Ghazali, Ibn Taymiyyah, and Ibn Qudamah, as well as the contributions of contemporary thought Wahbah Zuhaili and Umar Chapra. This study also traces the history of the implementation of the Islamic monetary system during the time of the Prophet and Khulafaur Rashidin which is based on bimetal standards (dinar-dirham), as well as examines the implementation of Islamic monetary policy in Indonesia through instruments such as sukuk, SBIS, and Islamic interbank money markets. The research methodology uses a qualitative approach with a literature review, analyzing primary and secondary literature to identify the foundations, pillars, and prospects of the Islamic monetary system. The results of the study show that the Islamic monetary system is able to integrate money creation control, risk-sharing-based policy transmission, real sector deepening, and governance based on sharia maqasid. Despite challenges such as low Islamic financial literacy and the need for regulatory harmonization, the prospects for the Islamic monetary system are very bright as an inclusive, sustainable, and equitable economic solution in the era of globalization and financial technology innovation